2017
DOI: 10.1590/0103-8478cr20160660
|View full text |Cite
|
Sign up to set email alerts
|

Morphological pattern of colonization by mycorrhizal fungi and the microbial activity observed in Barbados cherry crops

Abstract: Our objective was to evaluate the morphological pattern of colonization by arbuscular mycorrhizal fungi (AMF) as well as to study the microbiological activity of the soil on family farms where Barbados cherry was cultivated. Soil and root samples were selected from four areas in the municipality of Maranguape-CE where Barbados cherry was grown, which were named according to the age of plants in the following manner: A1-3, A2-3, and A3-3 (3 years), and A4-2 (2 years). After sampling, the arbuscular mycorrhizal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The potential for colonization depends on the plant and the type of fungus, in addition to the cultivation conditions and exposure time 47 50 . The Anta82 cultivar is more sensitive to drought stress (DS) and presented an increase in mycorrhizal colonization, especially under drought stress on days 3 and 7.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for colonization depends on the plant and the type of fungus, in addition to the cultivation conditions and exposure time 47 50 . The Anta82 cultivar is more sensitive to drought stress (DS) and presented an increase in mycorrhizal colonization, especially under drought stress on days 3 and 7.…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal colonization is the main means of symbiosis with the plant 42 , favoring both organisms involved. The colonization potential depends on the fungus and the plant used, in addition to the cultivation conditions and exposure time 43,19,44,45 . The cultivar Anta82 is more sensitive to water de cit and showed an increase in mycorrhizal colonization, especially under drought stress at 3 and 7 experimental days (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of AMF association in the cultivation of acerola cherry in Brazil was initially reported by Chu (1993), but studies on the effect of AMF inoculation with this fruit tree are still scarce. Silva Júnior et al (2017) evaluated the mycorrhizal colonization in barbados cherry cultures and verified the predominance of Paris type colonization pattern and that the soil phosphorus content may affect the colonization rate and the glomerospores density in the root system. Costa et al (2001) observed higher growth of acerola plants and shorter incubation time when inoculated with the fungus species Gigaspora margarita and Glomus etunicatum.…”
Section: Introductionmentioning
confidence: 88%